Determinan Minat Penggunaan E-Money Pada Mahasiswa Akademi Pariwisata Denpasar - I Wayan Wirawan; I Gusti Ayu Ratih Permata Dewi (Universitas Warmadewa, 2024)
This study aims to empirically test the influence of perceived benefits, perceived ease of use, service features, and security on the interest in using e-money among students of the Denpasar Tourism Academy. Perceived benefits, perceived ease of use, service features, and security as independent variables and interest in using e-money as dependent variables. The type of research used is quantitative research using questionnaire data collection methods and purposive sampling techniques. The number of samples used in this study was 100 respondents with the sample used being e-money users at Akademi Pariwisata. The data analysis method used is multiple linear regression analysis using Stata Version. The results of this study indicate that perceived benefits, perceived ease of use, and security have a positive and significant effect on interest in using e-money. This means that the more benefits, ease of use, service features, and security are felt, the greater the interest in using e-money.